ANALISIS VEGETASI GULMA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq) PADA TANAMAN BELUM MENGHASILKAN (TBM) dan TANAMAN MENGHASILKAN (TM) DI DESA PETAI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Kurnia Putrie Angga Pramana (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2017)
The aims of this study to the knowledge of the weeds mature and immature oil palm plantation(ElaeisquinensisJacq) in PetaisubdistrictSingingiHilir, Kuantansingingi. The study wasconducted from September to November 2016 by using quadrate method and survei withpurposive sampling technique.The results of the study show a weed on Immature of oil palmplantation , 14 species , as for the highest is panicumbrevifolium with 18,23 % SDR poaceaeweed of the family and lowest 0,67 % linearisgleichenia .A weed on palm oil plantationconsisting of 12 species , SDR the highest that is a kind of paspalumconjugatum , members ofthe family who dominant is the type poaceaewhile SDR lowest is melastomamalabatricum 1,19% of the family melastomaceae.Keyword: Weed, Immature of Oil Palm, Mature of Oil Palm, SDR